P 146 Differences in processing of action and semantic tool knowledge – evidence from fMRI and dynamic causal modelling. Issue 10 (October 2017) - Kleineberg, N.N.; Dovern, A.; Binder, E.; Grefkes, C.; Eickhoff, S.B.; Fink, G.R.; Weiss, P.H.
Abstract : Objective: Whether processing of function knowledge about tools (i.e., knowing what a tool is used for) draws upon action or semantic knowledge remains controversial. Methods: We investigated this issue using fMRI. 17 subjects performed three experimental tasks tapping into different aspects of tool knowledge. Data were analyzed using SPM and dynamic causal modeling (DCM). Results: The behavioral data and fMRI activation pattern suggested that function knowledge about tools was processed similarly as non-motor-related semantic tool knowledge (here: the monetary value of a tool) and could therefore be classified as "motor-related semantic knowledge", whereas action knowledge (i.e., how a tool is used) was processed differently. Processing of action knowledge activated areas of the ventro-dorsal stream (i.e., the lateral occipito-temporal cortex (LOTC) bilaterally, the left intraparietal sulcus (IPS), the left supramarginal gyrus (SMG), and the left inferior frontal gyrus (IFG)). In contrast, ventral stream areas were activated by the processing of semantic tool knowledge: the fusiform gyrus (FFG) bilaterally, the angular gyrus (ANG) bilaterally, and the medial prefrontal cortex (mPFC). Analyzing the effective connectivity between these areas with DCM revealed interactions between the processing streams (between LOTC and FFG as well as between SMG and ANG) and reciprocal modulatory effects. Conclusions: This fMRI-study substantiates that action and semantic knowledge about tools are processed along two separate routes and that function knowledge (i.e., knowing what a tool is used for) draws upon the semantic system. In addition, connectivity analysis with DCM revealed relevant interactions between the processing streams at lower and higher levels.